The brand communication of Сhinese companies in the media sphere of Belarus (on the example of Huawei) - Buride, Buride (Journal of the Belarusian State University. Journalism, 2019)
The purpose of the article is to identify and explore the characteristics of brand communication of the company Huawei in Belarus. For this reason the author analyzes the content (amount of mentions, quality characteristics) that is connected with this topic. The subject of the research is brand communication of the company Huawei in the media. The article contains information about the representation of the Huawei brand in the Belarusian media during the decade – from 2007 to 2017. The highlighted stages reflect the features of the spreading information about the Huawei brand. The obtained results have practical importance, on the one hand, for the further analysis of such a brand communication platform as media, on the other – for optimizing the activities of other Chinese companies working in Belarus today.
Keywords: brand; mass media; media sphere; transnational companies; brand communication